Asupan Protein Hewani berhubungan dengan Kejadian Stunting pada Balita di Wilayah Kerja Puskesmas Minggir: Asupan Protein Hewani Berhubungan dengan Stunting pada Balita di Wilayah Kerja Puskesmas Minggir - Haryani, Verrenisa Melati; Putriana, Dittasari; Hidayati, Ririn Wahyu (Universitas Airlangga, 2023)
Background: Stunting in children under fives years of age still become crucial problem. One of the factors that influenced directly to stunting is lack of nutritional intake especially protein. Most of protein consumed by under-fives children must be in high quality such as animal-based protein because it has more complete composition of essential amino acids than plant-based protein. Objectives: The study aimed to analyzed the association between animal-based protein and stunting in children in Primary Health Care of Minggir. Methods: This study was analytical observational with cross-sectional design. A total of 50 mothers that have 24–59 months old children were involve in this study and taken by using purposive sampling. Data of animal-based protein intake were collected by SQ-FFQ for the last three months. Height-for-age in z-score was used to determine stunting that were obtained from the last measurement and recorded in Maternal and Child Book. The association between stunting and the animal-based protein intake was analyzed descriptively through cross-tabulation. Results: More than half of under-five children were stunting (56%). Inadequate animal-based protein intake was observed in 46% of under-fives children. Sources of animal-based protein were eggs, chicken, catfish, ice cream and UHT milk. Children who have adequate animal-based protein intake were not stunted (67%), however children who have inadequate animal-based protein intake were stunted (83%). The prevalence of stunting in children who consume inadequate animal-based protein is 2 times greater than in children who consume adequate animal-based protein (PR: 2.478). Conclusions: Based on this study, animal-based protein intake is associated with stunting in under-fives children in Primary Health Care of Minggir. Mothers should improve their children's animal-based protein intake by local food sources supplied from side dishes to prevent stunting.